Analysis of the Performance of Diesel Engine Fueled using B50-B100 Biodiesel Based on Simulation - Semin Semin; Beny Cahyono; Himmawan Aan Listyanto; Rosli Abu Bakar (International Journal of Marine Engineering Innovation and Research, 2020)
This alternative research fuels in the form of biodiesel from waste cooking oil. In addition, the purpose of this study is to determine the effect of waste cooking oil biodiesel blends in the performance testing of a one-cylinder diesel engine simulation modeling. The method used by the author in this study is to use a simulation method. Performance-based diesel motor performance tests are performed using HSD, and also with variations of used cooking oil biodiesel fuel mixtures. From the performance test results at full load, it was found that the comparison of the value of the power mix of biodiesel waste cooking oil with HSD decreased power. At B50 decreased power (6.38%), B60 (7.6%), B70 (8.9%), B80 (10.2%), B90 (11.4%), and B100 (12.7%) at maximum RPM. The torque value obtained in the biodiesel fuel mixture also decreased compared to HSD in the same cycle. The lowest SFOC value is produced by HSD fuel. SFOC HSD value is lower than cooking oil biodiesel mixture which is higher (6.8%) B50 fuel, up (8.3%) B60, up (9.83%) B70, up (11.4%) B80, up (12.9%) B90, and up (14.5%) B100 at full load and maximum RPM conditions.